Legal Protection Of The Rights Of BPJS Kesehatan Patients In Orchid Rooms In Imelda Pekerja Indonesia General Hospital In 2023 - Ritonga, Abdul Malik; Manurung, Sarida Surya; Marito, Evelyn; Manurung, Jonni Sastra (Jurnal Media Informatika, 2024)
Legally protecting the rights of patients participating in the Health Social Security Administering Agency (BPJS) in obtaining health services, the government issued Law Number 24 of 2011 which determined that two State-Owned Enterprises, namely PT Askes (Persero) and PT Jamsostek (Persero) were changed to Public Service Materials to implement the five programs mandated by Law Number 40 of 2004, namely the Health Insurance program for BPJS Health and other programs are submitted to BPJS Employment. Hospitals in providing health services to BPJS participants are hampered by the lack of facilities and infrastructure in accordance with applicable standards. This research uses a descriptive research method with a qualitative approach, namely research conducted to systematically, factually and accurately describe or explain the facts and characteristics of a particular population. Based on the research, it was concluded that the legal protection of patient rights at RSU Imelda Pekerja Indonesia Medan was categorized as good. This is proven by the fulfillment of hospital rules and regulations, information on patient rights and obligations, information on diagnoses and procedures for medical procedures from health workers, patient complaints/complaints provided by the hospital.